A new change management approach for a law enforcement organization - Erciyes, Erdem (International journal of police science & management, 2018)
This research uses a pilot study to investigate current change management implementation in a law enforcement organization. Based on the findings, a new change management approach is established for a law enforcement organization. The core research question that guides this study is: ‘How can change management be implemented successfully in a law enforcement organization?’. Taking into consideration the research aim, type and size of the sample, and to gain different and in-depth knowledge of the change management phenomenon, the operations division of the Turkish gendarmerie was chosen as the sphere of interest and semi-structured interviews as the research method. The results present a new change management model for the chosen division. The main original contribution is first Ackerman’s change categorization at a law enforcement organization [Ackerman, L. (1986) Development, transition or transformation: the question of change in organization. OD Practitioner 18(4): 1-8], and then developing a new change management approach for each type of change category in this context.